Research on Safety Design Technology of High-power Lithium Ion Traction Battery System for Locomotive and EMU - Changfu PENG; Pinghua WANG; Guofu HE (机车电传动)
The application characteristics of lithium-ion power battery systems in the field of rail transit was introduced. The safety principles and requirements of high-power lithium-ion power batteries in locomotives and EMU were briefly introduced. The safety design technical guidelines for the use of active protection and passive protection for the lithium-ion power battery system were proposed, and relevant tests were carried out to verify. The research results showed that the safety design concept of active protection and passive protection could greatly improve the safety redundancy of the lithium battery system in locomotives and EMU applications.